Overweight, obesity and self-esteem of adolescents in a rural area of Ecuador - Castelo-Rivas , Walter (2023)
Objective. To determine the levels of overweight, obesity and self-esteem of adolescents in the rural parish of Valle Hermoso, Santo Domingo de los Colorados (Ecuador). Methods. The study was quantitative, with descriptive scope and transectional design. It was applied to 384 students of the Valle Hermoso Educational Unit, in the Province of Santo Domingo, Ecuador. A survey with 10 questions taken from Rosemberg's questionnaire to explore self-esteem was used. The internal consistency test of the instrument was developed through a Cronbach's alpha test; the data were analyzed at a descriptive level. Results. 13% of the students were  underweight, 61% were normal  weight, and 26% showed levels of overweight and obesity (mild, medium and morbid). In turn, it was identifed that the highest rates of self-esteem affection (medium and low) were found in adolescents with overweight and mild obesity. Conclusions. There is evidence of a greater presence of low self-esteem in overweight adolescents, and as the levels of obesity increased, their self-esteem increased, suggesting that they were beginning a process of acceptance of their physical appearance.